Tehnični vidiki dolgoročnega ohranjanja elektronske pošte - Krivec, Klavdija (Moderna arhivistika, 2018)
As a part of further development of the e-ARH.si project, based on the Strategy and Implementation Plan for the Development of the Slovenian Electronic Archives for the period 2016 - 2020, the preparation of solutions for the long-term email preservation is in progress. Article summarizes e-mail format issues, the possibility of transformation into archival formats and their validation. According to the survey, the authors focused on an email solution for the most frequently used email applications of our creators, IBM Lotus Notes and Microsoft Outlook. Possible scenarios of exports and conversions were designed for the purpose of making further decisions in the selection of appropriate technical solutions for the long-term email preservation at creators and in archival institutions.
Keywords: dolgoročna hramba-pošte; email formats conversion; long-term email preservation; PDF/A format; pretvorba formatov e-pošte; project e-ARH.si: ESS 2016-2020; projekt e-ARH.si: ESS 2016-2020